2006
DOI: 10.1530/eje.1.02170
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adrenomedullin in adipose tissue of lean and obese women

Abstract: Objective: Adrenomedullin (AM), a potent vasodilatator and antioxidative peptide, was shown recently to be expressed by adipose tissue. The aim of our study was to investigate the precise localization of AM within human adipose tissue, and to examine AM regulation in obesity. Design: Subcutaneous (SC) and omental (OM) adipose tissues from 9 lean and 13 obese women were profiled for AM expression changes. Preadipocytes from human adipose tissue were isolated and differentiated under defined adipogenic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…2d-f). By contrast, we detected adrenomedullin, as already reported [25], in nonfat-filled cells (Fig. 2d-f).…”
Section: Cd40 Is Expressed By Human Adipocytessupporting
confidence: 81%
“…2d-f). By contrast, we detected adrenomedullin, as already reported [25], in nonfat-filled cells (Fig. 2d-f).…”
Section: Cd40 Is Expressed By Human Adipocytessupporting
confidence: 81%
“…We believe that the development of insulin resistance during obesity may lead to an effective increase in adrenomedullin plasma concentration because the peptide would no longer be negatively controlled by insulin. This hypothesis is supported by recent results, demonstrating a positive correlation of adrenomedullin levels in omental adipose tissue with BMI and homeostasis model assessment index in obese patients with no endocrine, cardiovascular, hepatic, renal, or inflammatory disease (10).…”
supporting
confidence: 74%
“…Li et al (14) studied the expression of AM and resistin in 3T3-L1 preadipocytes and adipocytes by Northern blot analysis and showed that AM mRNA was expressed in 3T3-L1 preadipocytes but was undetectable in adipocytes, whereas resistin mRNA was not detected in 3T3-L1 preadipocytes but was expressed in adipocytes. It was also reported that preadipocytes at early differentiation stages secreted AM, but mature adipocytes did not secrete AM (34). In contrast, a recent study showed that the expression of AM mRNA increased in human mesenchymal stem cell-derived adipocytes at days 4,8,12, and 18 (16).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies in humans showed that plasma AM correlates with body mass index, and circulating AM is elevated in overweight patients with essential hypertension (34) and is decreased with a reduction of body weight by a hypocaloric diet (18), suggesting a role of AM in human adipose tissue.…”
mentioning
confidence: 99%